2016
DOI: 10.17521/cjpe.2015.0357
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of broad-leaf and Korean pine mixed forests at different successional stages to climate change in the Shengshan Nature Reserve of Heilongjiang Province, China

Abstract: Aims This research examined the different response of tree growth to climate change at the early, middle, late and matured successional stages of Korean pine (Pinus koraiensis) and broadleaf mixed forest. Methods This research used dendroecological methods to analyze radial growth at different successional stages of Korean pine forests in response to climatic change in the Shengshan Nature Reserve of Heilongjiang. Important findings Chronology statistics indicated that the sensitivity of radial growth to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For instance, Liang et al . 18 found that MS and SD decrease from early- to late-successional forests in a same site in northeast China. These results suggest that species identity may be another important factor affecting MS and SD in addition to environmental condition.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…For instance, Liang et al . 18 found that MS and SD decrease from early- to late-successional forests in a same site in northeast China. These results suggest that species identity may be another important factor affecting MS and SD in addition to environmental condition.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, on an arid mountain in northwest China, MS and SD decreased while tree height increased with higher altitude 27 . In another study along a successional series, MS and SD decreased from early- to late-successional forests, accompanied by an increase in forest height towards late-successional forests 18 . Nevertheless, the potential role of forest height was not explored in these studies.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This is because the growth and mortality of large trees are more sensitive to water deficit than smaller trees as a result of their high stature (which lead to greater difficulty in vertical water transportation to canopy). Northeast China has experienced the most drastic climate warming in China and the related drought trends is also evident in the past decades 36 , which have showed clear negative impacts on forest growth 37 . Our results suggest the need for further examining the role of large trees in forest dynamics, and the conservation of large trees in response to climate change.…”
Section: Discussionmentioning
confidence: 99%